Analysis Method of Transfer Pricing Used by Multinational Companies Related to Tax Avoidance and its Consistencies to the Arms Length Principle - Sari, Nuraini; Hunar, Ririn Susanti (Bina Nusantara University, 2015)
The purpose of this study is to evaluate about how Starbucks Corporation uses transfer pricing toÂ minimize the tax bill. In addition, the study also will evaluate how Indonesiaâs domestic rules can overcome theÂ case if Starbucks UK case happens in Indonesia. There are three steps conducted in this study. First, usingÂ information provided by UK Her Majestys Revenue and Customs (HMRC) and other related articles, findÂ methods used by Starbucks UK to minimize the tax bill. Second, find Organisation for Economic Co-Operation and Development (OECD) viewpoint regarding Starbucks Corporation cases. Third, analyze howÂ Indonesiaâs transfer pricing rules will work if Starbucks UKâs cases happened in Indonesia. The results showedÂ that there were three inter-company transactions that helped Starbucks UK to minimize the tax bill, such asÂ coffee costs, royalty on intangible property, and interest on inter-company loans. Through a study of OECDâsÂ BEPS action plans, it is recommended to improve the OECD Model Tax Convention including IndonesiaâsÂ domestic tax rules in order to produce a fair and transparent judgment on transfer pricing. This study concludedÂ that by using current tax rules, although UK HMRC has been disadvantaged because transfer pricing practicesÂ done by most of multinational companies, UK HMRC still cannot prove the transfer pricing practices are notÂ consistent with armâs length principle. Therefore, current international tax rules need to be improved.